2020
DOI: 10.3390/children7030023
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Social Support on Physical Activity in Chinese Adolescents: The Mediating Role of Exercise Self-Efficacy

Abstract: The purpose of this study was to examine the associations of social support and self-efficacy with physical Activity (PA) and the mediating effect of self-efficacy on the relationship between social support and PA in Chinese adolescents. Participants included a total of 2341 Chinese adolescents (aged 12.75 ± 1.46 years). Self-reported instruments, including the physical activity questionnaire for adolescents, the social support revalued scale and the exercise self-efficacy scale, were used to measure physical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
40
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(42 citation statements)
references
References 46 publications
2
40
0
Order By: Relevance
“…Results of the current study are in line with Seabra et al [107] who examined correlates of PA in schoolchildren aged 8-10 years, and found that perceived acceptance by peers in sports, and parental encouragement was positively related to PA in girls (n = 683). Some recent evidence would suggest that social support is a potentially important mediator of increased PA in young people [108][109][110][111], and has been targeted by several intervention programs [112,113].…”
Section: Discussionmentioning
confidence: 99%
“…Results of the current study are in line with Seabra et al [107] who examined correlates of PA in schoolchildren aged 8-10 years, and found that perceived acceptance by peers in sports, and parental encouragement was positively related to PA in girls (n = 683). Some recent evidence would suggest that social support is a potentially important mediator of increased PA in young people [108][109][110][111], and has been targeted by several intervention programs [112,113].…”
Section: Discussionmentioning
confidence: 99%
“…This finding aligns with a previous qualitative study conducted among girls where the researchers found a sense of self when active (such as being motivated to be active, enjoying PA, being confident in PA skills, and having PA skills judged by peers), and changes in social support from peers and family during the transition were related to their participation in PA [ 9 , 15 ]. In addition, it is well-established that the influence of peers increases during adolescence and influences adolescents’ PA [ 34 , 35 , 36 , 37 , 38 , 39 ]. Similarly, our study showed peers influenced PA participation after transition in a sample of boys and girls, but we also found athletic identity was in a state of flux during the transition.…”
Section: Discussionmentioning
confidence: 99%
“…Understanding the environmental factors that influence adolescents’ levels of PA during the transition from elementary to secondary school is complex as this study identified a number of intrapersonal and environmental factors that changed during this period. Given our understanding of the environmental factors that influence adolescents’ PA [ 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 54 , 55 , 56 ], it was not surprising that changes in the school, social, and household environments were highlighted as influencing adolescents’ PA during transition. Studies that examine factors associated with youth PA during the transition from elementary school to secondary school are relatively rare, and this paper addresses an important gap in the literature.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Social support is not an obligation but a responsibility. Social support has been conceptualized as information leading the individual to believe that he or she is cared for and loved, esteemed and valued, and belongs to a network of communication and mutual obligation [ 39 , 40 ]. Social support could also be defined as the assistance based on responsibility, provided to the individual by the people around her/him.…”
Section: Introductionmentioning
confidence: 99%